Organic effects of associating paclitaxel with a lipid-based nanoparticle system on a nonhuman primate, Cebus apella - Feio DC (Dove Medical Press, 2017)
Danielle Cristinne Azevedo Feio,1 Nayara Cristina Lima de Oliveira,1 Edmundo Luis Rodrigues Pereira,1 Aleksandra Tiemi Morikawa,2 José Augusto Pereira Carneiro Muniz,3 Raquel Carvalho Montenegro,1 Ana Paula Negreiros Nunes Alves,4 Patrícia Danielle Lima de Lima,5 Raul Cavalcante Maranhão,2 Rommel Rodríguez Burbano1 1Human Cytogenetics Laboratory, Institute of Biological Sciences, Federal University of Pará, Belem, 2Heart Institute, University of Sao Paulo Medical School Hospital, Sao Paulo, 3Evandro Chagas Institute, Primate National Center, Ananindeua, 4Department of Clinical Dentistry, Health Sciences Center, Federal University of Ceará, Fortaleza, 5Molecular Biology Laboratory, Post Graduate Program of Amazon Parasitic Biology, Biological and Health Sciences Center, State University of Pará, Belem, Brazil Abstract: Lipid-based nanoparticle systems have been used as vehicles for chemotherapeutic agents in experimental cancer treatments. Those systems have generally been credited with attenuating the severe toxicity of chemotherapeutic agents. This study aimed to investigate the effects of associating paclitaxel (PTX) with a lipid-based nanoparticle system on a nonhuman primate, Cebus apella, documenting the toxicity as measured by serum biochemistry, which is a detailed analysis of blood and tissue. Eighteen C. apella were studied: three animals were treated with cholesterol-rich nanoemulsion (LDE) only, without PTX, administered intravenously every 3 weeks, during six treatment cycles; six animals were treated with PTX associated with LDE at the same administration scheme, three with lower (175 mg/m2) and three with higher (250 mg/m2) PTX doses; and six animals were treated with commercial PTX, three with the lower and three with the higher doses. In the LDE-PTX group, no clinical toxicity appeared, and the weight–food consumption curve was similar to that of the controls. Two animals treated with commercial PTX presented weight loss, nausea and vomiting, diarrhea, skin flaking, 70% loss of body hair, and decreased physical activity. The use of LDE as a carrier at both lower and higher doses reduced the toxicity of the drug in this species, which is closely related to human subjects. This was observed not only by clinical, biochemical, and hematological profiles but also by the histopathological analysis. The results of this study support the assumption that lipid-based nanoparticle systems used as drug carriers can serve as valuable tools to decrease the toxicity and increase the safety of chemotherapeutic agents. Keywords: nanoparticles, LDE, paclitaxel, toxicity, Cebus apella